Ready-to-use mesoporous mineralized silk fibroin microspheres and application thereof

By using silk fibroin methacrylamide to prepare mesoporous mineralized microspheres, the problem of rapid release and short retention time of existing BMP-2 controlled release carriers was solved, and the long-term low-volume sustained release and bone regeneration promotion effect of BMP-2 was achieved.

CN119548673AActive Publication Date: 2025-03-04ZHEJIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411577988.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-03-04
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The existing BMP-2 controlled release carriers have problems such as rapid release, short retention time, and complex carrier components. It is difficult to achieve long-term, low-volume sustained release of BMP-2, and is not conducive to large-scale production and rapid application.

Method used

Silk fibroprotein methacrylamide as raw material, ready-to-use dry mesoporous mineralized silk fibroprotein microspheres (mSilMA) were prepared by bionic mineralization method and critical point drying method. The microspheres had mesoporous channel structure and mineralized coating, which improved the load efficiency and sustained release control of BMP-2.

Benefits of technology

Long-term low-dose sustained release of BMP-2 was achieved, and the cumulative release of only about 2% in 4 weeks in vitro was avoided, early sudden release was maintained, the biological activity of BMP-2 was promoted, and bone regeneration was promoted, and it had good biocompatibility and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548673A_ABST
    Figure CN119548673A_ABST
Patent Text Reader

Abstract

The invention provides ready-to-use mesoporous mineralized silk fibroin microspheres and application thereof. SilMA hydrogel microspheres are prepared by a photo-crosslinking oil / water emulsification method, and then dry mesoporous mineralized SilMA microspheres (mSilMA for short) are prepared by combining biomimetic mineralization and critical point drying methods. A silk fibroin material which is not easy to degrade and has good biocompatibility is selected as a carrier, so that the problems that BMP-2 is easy to lose and cannot be retained for a long time are solved; a calcium phosphate coating is formed through biomimetic mineralization, so that efficient loading and controlled release of BMP-2 are realized; the critical point is dried to form a mesoporous structure, which is beneficial to drug loading and release. The mSilMA is applied to BMP-2 loading and controlled release, the protein loading efficiency is high, and long-acting low-amount slow release can be achieved. The composition is simple in component, mild in preparation condition and easy to obtain, provides a new way for bone defect repair, and has a wide clinical application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application for the invention patent with application number: 202411111857.0 and invention name: "A ready-to-use mesoporous mineralized silk protein microsphere and its preparation method and application". Technical Field

[0002] The invention belongs to the field of biomedical materials, and in particular relates to ready-to-use mesoporous mineralized silk fibroin microspheres and applications thereof. Background Art

[0006] In addition to the collagen-based and calcium-phosphorus-based BMP-2 bone implants that have been clinically transformed, many new BMP-2 carriers that promote bone regeneration have been reported in the literature. However, their ingredients are complex, and they require more preparation processes. They are not easy to obtain immediately, and their clinical transformation is slow. For example, Liu et al. prepared a PLGA scaffold, treated it with plasma technology to increase the surface hydrophilicity, then immersed it in a mixture of zwitterionic monomers, crosslinkers and photoinitiators, and formed a zwitterionic hydrogel coating on the surface of the PLGA scaffold by ultraviolet curing technology. The PLGA / zwitterionic hydrogel was further immersed in a calcium phosphate mineralization solution to form calcium phosphate mineralization on the surface of the scaffold. The mineralized PLGA / zwitterionic hydrogel was freeze-dried to form a scaffold that can release BMP-2 in low amounts. This design is to achieve controlled release of BMP-2 through the charge interaction between zwitterionic hydrogel and BMP-2 and the strong affinity of calcium phosphate mineralization for BMP-2 (Literature source: Liu P, Bao T, Sun L, et al. Insitu mineralized PLGA / zwitterionic hydrogel composite scaffold enables high-efficiency rhBMP-2release for critical-sized bone healing[J].BiomaterialsScience,2022); however, the PLGA scaffold has the following disadvantages: first, the preparation process of the PLGA scaffold after multi-step processing is cumbersome and complicated, time-consuming, and costly, which is not conducive to large-scale production and rapid application; second, the structure and performance of the scaffold may be affected by multiple processing steps, and there are problems with stability and repeatability; in addition, due to the multiple components and complex processes involved in the preparation process, the biocompatibility and biodegradability of the scaffold may also be affected to a certain extent. Therefore, the PLGA scaffold cannot achieve the effect of rapid preparation and efficient mass production, and it is difficult to quickly meet the immediate needs of bone defect repair in actual clinical applications, and its role in rapid transformation and application in clinical treatment is limited.

[0007] Therefore, there is an urgent need to find a biomaterial carrier that can solve the problems of rapid release, short retention time, and complex carrier components of existing BMP-2 controlled-release carriers. It has the characteristics of simple preparation process, low cost, and good biocompatibility. It can achieve long-term, low-volume sustained release of BMP-2, avoid early burst release, maintain its biological activity, and promote bone regeneration. It has good clinical transformation potential and application prospects, and can provide a more effective solution for the treatment of bone defects. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the present invention provides a ready-to-use mesoporous mineralized silk fibroin microsphere and its preparation method and application. With silk fibroin methacrylamide as raw material, the biomimetic mineralization method and the critical point drying method are comprehensively utilized to successfully prepare the ready-to-use dry mesoporous mineralized silk fibroin microsphere (mSilMA); silk fibroin is a regular oriented fiber structure formed by hierarchical assembly of nanofibrils, containing a large number of polar amino acids, these hydrophilic and polar groups can be tightly combined with positive and negative ions, and can induce inorganic substances to nucleate and grow on the silk fibroin template. The effective loading rate of BMP-2 (500ng) per milligram of mSilMA microsphere prepared by the present invention reaches more than 85%, and the in vitro sustained release test finds that the mSilMA microsphere can continuously release BMP-2 in low amounts, and the cumulative release of BMP-2 in vitro for 4 weeks is about 2%, realizing the in vitro long-term low-amount release of BMP-2, and no early burst release occurs.

[0009] In order to achieve the above object, the present invention adopts the following scheme:

[0010] On the one hand, the present invention provides a ready-to-use mesoporous mineralized silk fibroin microsphere, wherein the main component of the ready-to-use mesoporous mineralized silk fibroin microsphere has a fiber structure, the microsphere has a mesoporous channel structure, and the surface of the microsphere includes a mineralized coating.

[0011] Furthermore, the main component includes silk fibroin; the silk fibroin is silk fibroin methacrylamide.

[0012] Furthermore, the mineralized coating is needle-shaped calcium phosphate; and the pore size of the mesoporous channel is 5-50 nm.

[0013] In order to solve the many problems of rapid release, short retention time and complex carrier components of BMP-2 controlled-release carriers in the current bone repair field, based on the characteristic of silk fibroin with natural fiber structure, the present invention proposes a ready-to-use mesoporous mineralized silk fibroin microsphere that can release bone morphogenetic protein in a long-term and low amount. By using silk fibroin methacrylamide as the main component and utilizing its fiber structure characteristics, the microspheres are formed into a mesoporous channel structure through a specific preparation method, and a needle-shaped calcium phosphate mineralized coating is generated on the surface of the microspheres.

[0014] The loading efficiency of BMP-2 by the microspheres prepared by the present invention can reach more than 85%, and can achieve long-term low-volume sustained release of BMP-2, with the cumulative release of only about 2% in vitro for 4 weeks. In addition, the microspheres have good biocompatibility and stability, can be stably present in the implantation site of bone defects for a long time, and continuously play a role in promoting bone repair and regeneration, providing an efficient and promising solution for the treatment of bone defects.

[0015] Furthermore, the ready-to-use mesoporous mineralized silk microspheres are loaded with active proteins, and the active proteins include any one or more of BMP-2, VEGF, FGF, and TGF-β.

[0016] Furthermore, the active protein is BMP-2.

[0017] The ready-to-use mesoporous mineralized silk microspheres are loaded with active proteins, including bone morphogenetic protein-2 (BMP-2), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), transforming growth factor-β (TGF-β) and the like.

[0018] In the present invention, the microspheres are particularly selected to be loaded with BMP-2 because the existing BMP-2 controlled release carriers have problems such as rapid release, short retention time, and complex carrier components. When the microspheres of the present invention are loaded with BMP-2, the loading efficiency of BMP-2 can be significantly improved, and its long-term low-volume sustained release can be achieved. Specifically, the mesoporous structure of the microspheres increases the specific surface area, providing more binding sites for BMP-2, thereby increasing the loading amount. At the same time, the mineralized coating on the surface of the microspheres effectively controls its release rate through interaction with BMP-2, avoids early sudden release, and allows BMP-2 to continue to play a role for a long time, promoting the regeneration and repair of bone tissue. In addition, the good biocompatibility and stability of silk fibroin ensure the safety and effectiveness of the microspheres in vivo, providing an efficient and reliable solution for the treatment of bone defects.

[0019] In some embodiments, the present invention compares and screens the BMP-2 protein loading rate and long-term low-volume sustained-release capacity of microspheres with different main components, different drying methods, different mineralization methods, different mineralization concentrations, undried microspheres and unmineralized microspheres, and the experimental results show that only when silk fibroin methacrylamide is used as the main component, the critical drying method is used for drying, the Ca / P method is used at the same time, and the mineralization solution concentration is 1 times the Ca / P mineralization solution, can mSilMA microspheres with surface-penetrating mesoporous channels and intact structures be successfully prepared, and the BMP-2 protein loading rate can reach more than 85%, while BMP-2 can be continuously released in low amounts, with a cumulative release of about 2% of BMP-2 in vitro for 4 weeks; and when any of the conditions is replaced arbitrarily, the effect of the present invention cannot be achieved.

[0020] In the field of bone repair, achieving long-term, low-volume sustained release of bone morphogenetic protein (BMP-2) has always been a key issue to be solved. The present invention aims to overcome this problem by using silk fibroin as raw material and combining biomimetic mineralization method and critical point drying method to successfully prepare ready-to-use mesoporous mineralized silk fibroin microspheres (mSilMA).

[0021] Silk fibroin as a raw material is the basis of the present invention, which has a unique fiber structure and excellent biocompatibility. If this raw material is missing or replaced with other materials, it is impossible to provide a suitable carrier for the subsequent mineralization and drying steps, and it is impossible to achieve the loading and controlled release of BMP-2.

[0022] The biomimetic mineralization method (calcium chloride / phosphoric acid-ammonia water reaction method) is indispensable in the preparation process. This method forms a calcium phosphate mineralized coating on the surface of silk fibroin microspheres. On the one hand, the strong affinity of calcium phosphate for BMP-2 is used to achieve efficient loading, and on the other hand, the release rate of BMP-2 is greatly reduced. If there is no biomimetic mineralization step or other mineralization methods and mineralization concentrations are used, a mineralized coating cannot be formed. Even if silk fibroin raw materials and critical point drying methods are used, due to the lack of strong affinity and controlled release for BMP-2, effective loading and long-term stable controlled release of BMP-2 cannot be achieved, and the effect of long-term low-volume sustained release cannot be achieved.

[0023] The critical point drying method is a key step in forming a mesoporous structure. The mesoporous channel structure can provide more binding sites for BMP-2, which is conducive to the retention and sustained release of cytokines and enhances the interaction between the microspheres and the body. If only silk fibroin raw materials and bionic mineralization methods are used, there is no critical point drying to form a mesoporous channel structure, the cytokine binding sites are limited, and the efficient loading and slow sustained release of BMP-2 cannot be achieved; and when other drying methods are used, under the same technical solution of the present invention, mesoporous channels cannot be formed at all.

[0024] In summary, only by using silk fibroin as raw material and synergistically adopting the bionic mineralization method (calcium chloride / phosphoric acid-ammonia water reaction method) and the critical point drying method, all three of which are indispensable, can we successfully prepare mSilMA with the best effect, achieve long-term, low-volume sustained release of BMP-2, high loading efficiency and good biocompatibility, and provide an ideal material for bone repair.

[0025] In another aspect, the present invention provides a method for preparing ready-to-use mesoporous mineralized silk fibroin microspheres, comprising the following steps:

[0026] (1) Preparation of SilMA hydrogel microspheres;

[0027] (2) mineralizing the SilMA hydrogel microspheres;

[0028] (3) drying the mineralized SilMA hydrogel microspheres to obtain dry mesoporous mineralized SilMA microspheres;

[0029] In the step (1), SilMA hydrogel microspheres are prepared by UV cross-linking oil / water emulsification and mechanical stirring; in the step (2), Ca / P method is used for mineralization; in the step (3), critical point drying method is used for drying. Gelatin methacrylamide hydrogel microspheres (GelMA for short) undergo the same ethanol gradient dehydration and critical point drying, but do not form a surface-penetrating mesoporous structure, but present a non-porous structure; while the surface of SilMA microspheres forms an interconnected mesoporous channel structure. Therefore, it can be preliminarily known that not all materials can form mesopores through critical point drying.

[0030] In some embodiments, when preparing SilMA, different preparation methods are screened, and the experimental results show that: the SilMA prepared by the UV-crosslinked oil / water emulsification method (mechanical stirring) of the present invention has significantly improved microsphere yield and microsphere sphericity, which has significant advantages in both yield and sphericity compared to the microspheres prepared by the photo-crosslinked 3D printing technology; while the microspheres prepared by the photo-crosslinked 3D printing technology are easy to adhere and cannot be separated; the sphericity is poor, generally in the form of cylinders. In addition, the mechanical stirring method used in the present invention can change parameters such as the oil / water ratio and the stirring speed, thereby successfully preparing microspheres with a particle size range of 1μm-1000μm, but the photo-crosslinked 3D printing technology cannot print and form microspheres below 100μm, and can only print microspheres of specific sizes, such as 200μm, 400μm, etc.; in addition, the yield of microspheres is limited by the volume of the printing ink and the size of the printable stage.

[0031] Therefore, it is preferred to prepare SilMA by UV-crosslinking oil / water emulsification method (mechanical stirring), which has the best yield, sphericity, controllable particle size range and other properties, can better meet the needs of practical applications, and lays a solid foundation for the subsequent preparation of mSilMA with excellent performance.

[0032] In some embodiments, in order to obtain the microspheres with the best performance in the present invention that can release BMP-2 in a long-term and low amount, the main components of the microspheres are first screened, and the main components of the microspheres are silk fibroin methacrylamide and gelatin methacrylamide, respectively, to prepare GelMA microspheres and SilMA microspheres, respectively. The experimental results under scanning electron microscopy show that after the same ethanol gradient dehydration and critical point drying, the GelMA hydrogel microspheres do not form a surface-penetrating mesoporous structure, but present a non-porous structure; while the surface of the SilMA microspheres forms an interconnected mesoporous channel structure. Therefore, it can be preliminarily known that not all materials can form mesopores through critical point drying. Based on the above results, the inventors speculate that it is precisely because silk fibroin has an original fiber structure that its own fiber network can be reproduced through critical point drying; gelatin itself does not have a fiber structure. At the same time, during the ethanol gradient dehydration process, as water is lost, the hydrogel network structure of gelatin itself gradually becomes dense, and then through critical point drying, the fiber network structure can no longer appear, and the surface is dense and non-porous; therefore, it is speculated that if the material itself has a fiber structure, a porous structure can be generated through critical point drying; if the material itself does not have a fiber structure, a porous structure cannot be generated through critical point drying.

[0033] In the present invention, the mesoporous channel structure is extremely important for preparing hydrogel microspheres that can release BMP-2 in a long-term and low amount. Mesopores can significantly increase the drug loading capacity, and the interconnected mesoporous channels are conducive to the loading and slow and continuous release of cytokines, avoiding sudden release, prolonging the action time of BMP-2, improving the utilization efficiency and therapeutic effect of BMP-2, and providing stable support for bone repair; at the same time, it is conducive to the material exchange and information transmission between the microspheres and the surrounding environment, which is conducive to the growth and proliferation of cells in the interstitial space of the microspheres, and improving the adaptability and biocompatibility of the microspheres in the body.

[0034] Therefore, SilMA, which can form mesopores, is preferred as the main component of the microspheres to achieve more ideal drug loading and controlled release effects, providing strong technical support and innovative ideas for the development of bone tissue engineering and other fields.

[0035] In some embodiments, during the preparation of SilMA microspheres, the drying method of SilMA hydrogel microspheres was screened, and the experimental results showed that: the dry SilMA microspheres prepared by the critical point drying method did not have adhesion phenomenon, and the surface of the microspheres had uniformly distributed mesopores; the uniform mesoporous structure was conducive to the loading and sustained release of drugs, and could provide a more stable and controllable release environment for drugs such as BMP-2, so as to better play the role of BMP-2 and improve the therapeutic effect; while the dry SilMA microspheres prepared by the freeze drying method not only failed to form mesopores on the surface of the microspheres, resulting in limited BMP-2 loading and sustained release performance, but also adhesion between the microspheres, resulting in a rough surface; this rough surface and adhesion phenomenon may affect the dispersibility and stability of the microspheres, and thus affect their effect in practical applications. Therefore, it is preferred to prepare dry SilMA microspheres by the critical point drying method.

[0036] In some embodiments, different mineralization methods are screened during the preparation of mSilMA microspheres. Experimental results show that the Ca / P method can form a more uniform and denser calcium-phosphate mineralized coating on the surface of SilMA microspheres, and the more uniform and denser calcium-phosphate mineralized coating can enhance the stability and mechanical strength of the microspheres, improve the compatibility and binding ability of the microspheres with bone tissue, and help to better promote bone regeneration and repair processes; in addition, the uniform and high-density coating can more effectively control the release rate of BMP-2, provide a more stable load and release environment for BMP-2, thereby improving the therapeutic effect of BMP-2. Therefore, the Ca / P method is preferred as the mineralization method of SilMA microspheres.

[0037] Furthermore, the mineralization concentration is 1 times Ca / P mineralization solution, and in the 1 times Ca / P mineralization solution, the molar ratio of calcium chloride to phosphoric acid is 1.5-2.0.

[0038] At the same time, in some embodiments, in the process of preparing mineralized SilMA hydrogel microspheres by the Ca / P method, the concentrations of different Ca / P mineralizing solutions were screened, and the effects of different Ca / P mineralizing solution concentrations on SilMA microspheres and surface calcium-phosphorus mineralization layers were studied. The experimental results show that, while keeping other conditions unchanged, increasing the concentration of the Ca / P mineralizing solution will lead to the destruction of the microsphere structure. The calcium-phosphorus coating still maintains a needle-like structure. As the concentration of the Ca / P mineralizing solution increases, the coating density increases. However, 5 times and 10 times the Ca / P mineralizing solution significantly damage the microsphere structure. Therefore, 1 times the Ca / P mineralizing solution is preferred. At this concentration, the complete structure of the microsphere is retained, and a relatively evenly distributed needle-like calcium-phosphorus coating can exist on the surface of 20% SilMA microspheres, and the mesoporous channels of the microspheres themselves are not completely blocked by the needle-like calcium-phosphorus coating.

[0039] Moreover, at a Ca / P mineralization solution concentration of 1, the pore size of the dry mSilMA surface after mineralization and critical drying will be further reduced. This has the following advantages: (1) Better controlled release performance: smaller pore size can more effectively load and control the release rate and amount of drugs or cytokines, so that they can be released continuously and stably for a longer time, thereby improving the therapeutic effect; (2) Enhanced stability: smaller pore size may make the microsphere structure more stable, reduce the impact of the external environment on the internal loaded substance, and improve the stability of the microspheres during storage and use; (3) Improved selectivity: It can more selectively allow molecules of a specific size to pass through or be adsorbed, thereby achieving more accurate drug loading or dissociation; (4) Reduced burst release: Reduced the sudden large-scale release of drugs in the initial stage, making drug release more uniform and controllable; Therefore, it can be seen that in the present invention, mineralization treatment is an indispensable step. Only by mineralizing the SilMA hydrogel microspheres and using the Ca / P mineralization method with low calcium and phosphorus concentrations can the best mSilMA be prepared, achieving the best effect of optimizing the physical properties of the microspheres and the controlled release performance of the drugs, and providing a more ideal material selection for applications in related fields such as bone repair.

[0040] In some embodiments, in order to verify the necessity of the mineralization step for the preparation of mSilMA in the present invention, this example also focuses on the difference in the in vitro controlled release ability of BMP-2 by 20% mSilMA microspheres and 20% SilMA microspheres. The experimental results show that 20% mSilMA microspheres can sustain low-amount sustained release of BMP-2, with a cumulative release of about 2% of BMP-2 in vitro for 4 weeks, while 20% SilMA microspheres fail to release BMP-2 for a long time, reaching a release plateau in about 3 weeks, which may be because the adsorption / dissolution of the drug by the mesopores reaches a balance to some extent, resulting in incomplete release.

[0041] Preferably, in the 1x Ca / P mineralization solution, the molar ratio of calcium chloride to phosphoric acid is 1.5-1.7.

[0042] Furthermore, the immersion time of the mineralizing solution is 12 hours to 48 hours; in the Ca / P method, the volume fraction of the ammonia solution is 10% to 20%, and the ammonia solution action time is 30 minutes to 2 hours.

[0043] Furthermore, in the step (1), the concentration of the SilMA solution is 10%-30%; the dissolution temperature of the SilMA is 25°C-45°C; LAP solution is added to the SilMA solution as the aqueous phase, and the aqueous phase and the oil phase are stirred and mixed, and the final concentration of the LAP aqueous solution is: 0.1%-0.5%; the volume ratio of the oil phase to the aqueous phase is 1:1-10:1; in the oil phase, the mass ratio of Span 80 to liquid paraffin is 1:10-1:30; the stirring temperature is 25°C-45°C; the stirring time and ultraviolet irradiation time are 5-15min.

[0044] The LAP is lithium phenyl-2,4,6-trimethylbenzoylphosphinate.

[0045] In some embodiments, SilMA microspheres were prepared by photo-crosslinking oil / water emulsification-critical drying using SilMA solutions of different concentrations, and their swelling properties and surface pore sizes were statistically analyzed. The experimental results showed that: on the one hand, 10% SilMA microspheres had the strongest water absorption and swelling ability, and were easily soaked, swollen and broken within 1 week, and lost their structural integrity, which indicated that their stability was insufficient and not suitable for subsequent treatment; while there was no significant difference in the water absorption and swelling ability of 20% SilMA microspheres and 30% SilMA microspheres; on the other hand, according to the results of scanning electron microscopy, the surface pore size of 10% SilMA microspheres was the largest, with an average pore size of about 100nm, the surface pore size of 20% SilMA microspheres was about 20nm, and the surface average pore size of 30% SilMA microspheres was about 5nm, while the molecular diameter of BMP-2 was about 10nm. Combined with the partial effect of subsequent mineralization treatment on the surface pore size of SilMA microspheres, it is speculated that the pore structure of 30% SilMA microspheres after mineralization is not conducive to loading BMP-2. The 20% SilMA microspheres can both physically adsorb BMP-2 and limit its rapid release to a certain extent, which helps to achieve a better controlled release effect. Therefore, considering the swelling properties and surface pore size distribution of SilMA microspheres with different concentrations, the 20% SilMA microspheres are more balanced and ideal in terms of stability, BMP-2 loading and controlled release, so the 20% SilMA microspheres are preferred for the next step of biomimetic mineralization.

[0046] Preferably, the dissolution temperature of the SilMA is 25°C-30°C; and the stirring temperature is 25°C-30°C.

[0047] Furthermore, in the step (3), a gradient ethanol aqueous solution is used for dehydration, the microspheres are immersed in the ethanol aqueous solution for 15-30 minutes, and the critical point drying time is 3 hours to 5 hours.

[0048] Preferably, the critical point drying time is 3-5 hours.

[0049] In another aspect, the present invention provides a use of ready-to-use mesoporous mineralized silk fibroin microspheres for preparing a preparation for improving bone repair ability or promoting bone regeneration, wherein the ready-to-use mesoporous mineralized silk fibroin microspheres are prepared by the preparation method described in any one of the above technical schemes.

[0050] On the other hand, the present invention provides a use of ready-to-use mesoporous mineralized silk fibroin microspheres for preparing a preparation for improving the long-acting, low-dose sustained release ability of BMP-2 or reducing the burst release ability of BMP-2. The ready-to-use mesoporous mineralized silk fibroin microspheres are prepared by the preparation method described in any one of the above technical schemes.

[0051] In another aspect, the present invention provides a use of ready-to-use mesoporous mineralized silk fibroin microspheres for preparing a preparation for improving the protein loading rate of BMP-2, wherein the ready-to-use mesoporous mineralized silk fibroin microspheres are prepared by the preparation method described in any one of the above technical schemes.

[0052] On the other hand, the present invention provides a use of silk fibroin for preparing a preparation for improving the long-acting, low-dose sustained-release ability of BMP-2 or reducing the burst-release ability of BMP-2, in which silk fibroin is used as a raw material to prepare microspheres, and the microspheres are prepared by the preparation method described in any one of the above technical schemes.

[0053] In another aspect, the present invention provides a use of silk fibroin for preparing a preparation for improving the protein loading rate of BMP-2, wherein the preparation uses silk fibroin as a raw material to prepare microspheres, and the microspheres are prepared by the preparation method described in any one of the above technical schemes.

[0054] The beneficial effects of the present invention are:

[0055] 1. The present invention provides a ready-to-use mesoporous mineralized silk fibroin microsphere, a preparation method and application thereof. SilMA hydrogel microspheres are prepared by a photocrosslinking oil / water emulsification method. The method is simple to operate, easy to control, and can prepare a large number of microspheres with stable performance. The SilMA hydrogel microspheres are converted into mSilMA by combining a bionic mineralization method and a critical point drying method. The preparation process conditions are mild and will not damage the structure and performance of the microspheres, which is conducive to large-scale production and application. The ready-to-use dry mesoporous mineralized silk fibroin microspheres prepared by the present invention have a relatively simple composition and only contain silk-based microspheres and a mineralized coating on the surface of the microspheres.

[0056] 2. The present invention uses a silk fibroin material that is not easily degradable and has good biocompatibility as a delivery carrier of BMP-2. The prepared SilMA microspheres are not easily degradable, can stably exist in the bone defect implantation site, and continuously release BMP-2, thereby avoiding the problem of rapid loss of BMP-2 caused by easily degradable materials, inflammation caused by early large-scale release, and inability to achieve long-term therapeutic effects, thereby providing long-term and stable support for bone repair; at the same time, by performing bionic mineralization on the surface of the SilMA microspheres to form a calcium phosphate mineralized coating, on the one hand, efficient loading is achieved by utilizing the strong affinity of calcium phosphate substances for BMP-2, and on the other hand, the release rate of BMP-2 is greatly reduced, thereby solving the problem that simple calcium phosphate materials are easily degraded and cannot control the release of BMP-2 for a long time, thereby enabling BMP-2 to play a long-term and stable role and promote the regeneration and repair of bone tissue; and the critical point drying method is used to form a through-mesoporous channel structure in the SilMA microspheres, thereby providing an ideal structural basis for the loading and controlled release of drugs and proteins, and drugs or proteins can be captured in the mesopores by physical adsorption and diffuse release is achieved, thereby further enhancing the controlled release performance of the microspheres.

[0057] 3. In the present invention, the prepared mSilMA is applied to the loading and controlled release of BMP-2, and its protein loading efficiency can reach more than 85%, and the cumulative release in 4 weeks is only about 2%, realizing the long-term low-volume sustained release of BMP-2; the controlled release performance can effectively maintain the effective concentration of BMP-2 in the local area, reduce the dosage and frequency of drug use, reduce the cost of treatment and potential side effects, and provide an efficient, safe and economical solution for the treatment of bone defects. At the same time, it also provides an innovative, efficient and broad application prospect technical means for the field of bone defect repair, which is of great significance for improving the treatment effect of bone defects and improving the quality of life of patients. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 The present invention discloses a preparation process of dry mesoporous mineralized silk fibroin methacrylamide microspheres (mSilMA).

[0059] Figure 2 The surface morphology of GelMA microspheres and SilMA microspheres after critical point drying under a scanning electron microscope.

[0060] Figure 3 The surface morphology of dry SilMA microspheres prepared by freeze drying and critical point drying methods.

[0061] Figure 4 The results of the structure and content of calcium phosphate substances formed on the surface of SilMA microspheres using different mineralization methods.

[0062] Figure 5The effects of three concentrations of Ca / P mineralizing solution on the structure and surface mineralized coating of 20% SilMA microspheres.

[0063] Figure 6 A in FIG. 1 is the nitrogen physical adsorption test of dry mesoporous 20% SilMA microspheres (abbreviated as 20% SilMA).

[0064] Figure 6 Figure B is the nitrogen physical adsorption test of dry mesoporous mineralized 20% SilMA microspheres (abbreviated as 20% mSilMA).

[0065] Figure 6 C in the figure is the pore size distribution results of 20% mSilMA microspheres and 20% SilMA microspheres.

[0066] Figure 7 A in the figure is the morphology difference between 20% mSilMA microspheres and 20% SilMA microspheres.

[0067] Figure 7 B in FIG. 1 is the difference in the in vitro controlled release ability of BMP-2 between 20% mSilMA microspheres and 20% SilMA microspheres.

[0068] Figure 8 A in the figure is the swelling performance results of 10%, 20%, and 30% dry mesoporous SilMA microspheres.

[0069] Figure 8 B in the figure is the surface pore size distribution of 10%, 20%, and 30% SilMA microspheres obtained by statistical analysis of scanning electron microscopy results (obtained by critical drying).

[0070] Fig. 9 The surface morphology of 10%, 20%, and 30% dry SilMA microspheres (obtained by critical drying).

[0071] Fig.10 A in the figure is a light microscopic image of 20% SilMA hydrogel microspheres prepared by photo-crosslinking oil / water emulsification method (mechanical stirring).

[0072] Fig.10 Figure B is a light microscopy image of 20% SilMA hydrogel microspheres prepared by photo-cross-linking 3D printing technology. DETAILED DESCRIPTION

[0073] The present invention is described in detail below in conjunction with embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.

[0074] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0075] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0076] Glossary of relevant terms:

[0077] 1. Bionic mineralization: In the field of artificial material synthesis, bionic mineralization obtains inorganic or inorganic / organic composite materials with complex advanced structures and special biological functions by regulating the nucleation and growth of minerals such as calcium carbonate and calcium phosphate.

[0078] 2. Critical point drying method: To prevent the sample from being slightly deformed due to the rapid movement of the water interface during drying, the liquid in the sample is removed under a critical state without a gas-liquid interface. In traditional drying methods, liquid is directly converted into gas under high temperature conditions, which will produce a certain change in surface tension and may destroy the fine structure of the sample. For special samples, such as sol-gel, biological samples, and porous materials with unstable structures, using traditional drying methods to pretreat the sample will cause the sample structure to be damaged. In the critical point drying method, the medium adopts a phase change method of liquid carbon dioxide-supercritical carbon dioxide-gas carbon dioxide to reduce the surface stress of the interface to zero, which can preserve the fine structure of the sample.

[0079] 3. The main process of critical point drying samples: After the samples are dehydrated by gradient of 30%-50%-70%-90%-100% ethanol aqueous solution, they are placed in a critical point drying device (high-pressure closed container), injected with liquid carbon dioxide, and dried under the critical state of 31°C and 72.8 atmospheres.

[0080] Example 1 The best ready-to-use dry mesoporous mineralized silk fibroin microspheres of the present invention and the preparation method thereof

[0081] 1. Research ideas and process of the ready-to-use dry mesoporous mineralized silk fibroin microspheres of the present invention

[0082] In the current field of bone repair, BMP-2, as a key bone morphogenetic protein, plays an important role in promoting bone regeneration. However, existing BMP-2 controlled-release carriers have problems such as rapid release, short retention time, and complex carrier components, which seriously limit their clinical application effects.

[0083] In view of this, the present invention is committed to finding a new solution that can effectively solve these problems. After in-depth research and a large number of experiments, combined with a full understanding of silk fibroin, calcium-phosphorus materials and mesoporous structures, the present invention proposes an innovative concept for preparing ready-to-use mesoporous mineralized silk fibroin-based microspheres, and finally prepares a ready-to-use mesoporous mineralized silk fibroin microsphere by proposing a preparation method for ready-to-use mesoporous mineralized silk fibroin microspheres that can release bone morphogenetic protein in a long-term and low-volume sustained manner.

[0084] Silk fibroin is a natural high-molecular fibrous protein extracted from silk. It has adjustable mechanical properties, controllable degradation, low immunogenicity, and can be obtained at low cost. A variety of silk-based biomaterials have been approved for clinical use in my country, such as silk-based ligament grafts and long-term bioresorbable surgical meshes, indicating that silk-based derived scaffolds have great potential for clinical transformation. Kaplan et al. prepared hydroxyapatite particles wrapped with silk fibroin, which were combined with BMP-2 by silk fibroin coating. However, it was unable to achieve long-term low-volume sustained release of BMP-2 and could not meet the requirements of long-term stable release. The sustained release time was short, making it difficult to achieve the ideal therapeutic effect. (Ding ZZ, Fan ZH, Huang XW, et al. Bioactive natural protein–hydroxyapatitenano carriers for optimizing osteogenic differentiation of mesenchymal stem cells[J]. Journal of Materials Chemistry B, 2016.)

[0085] Calcium phosphate material is an attractive BMP-2 controlled release matrix, which can reversibly bind to proteins and interact physically, chemically and electrostatically with the characteristic conformation and amino groups of proteins. Studies have found that mineralized collagen scaffolds release about 80% of BMP-2 in vitro for 14 days. Since collagen scaffolds are easily degraded, it is impossible to extend the retention time of BMP-2, and it is difficult to achieve long-term and stable control of BMP-2 release, which cannot meet the needs of some applications that require long-term sustained release of BMP-2. (Yang HS, La WG, Bhang SH, et al. Apatite-coated collagen scaffold for bonemorphogenetic protein-2 delivery [J]. Tissue Engineering Part A, 2011)

[0086] Mesoporous materials have attracted much attention in the field of drug delivery due to their regular pore structure, relatively narrow pore size distribution, and large specific surface area. Drugs can be captured in the mesopores through the impregnation adsorption process and released by diffusion. Liu et al. used a mesoporous bioactive glass scaffold to adsorb BMP-2, but the initial release reached 27% after 1 day; therefore, it can be seen that the mesoporous structure is not effective in reducing the early burst release. Moreover, the adsorption / dissolution of drugs in the mesoporous structure easily reaches equilibrium in a certain period of time, resulting in incomplete release of BMP-2, which cannot fully exert the effect of the drug and makes it difficult to achieve a stable, continuous and complete release of BMP-2. (Liu Y, Yang Z, Wang L, et al. Spatiotemporal Immunomodulation Using Biomimetic Scaffold Promotes Endochondral Ossification-mediated Bone Healing[J]. Advanced Science, 2021 / / Le TT, et al. Delivery of poorly solubledrugs viamesoporous silica: Impact of drug overloading on release and thermal profiles[J].Pharmaceutics,2019 / / He S,Pan H,Zhang J.Advances of typical mesoporousmaterials and the application in drug delivery[J].Materials Research Express,2023.)

[0087] Therefore, in the present invention, silk fibroin methacrylamide (SilMA for short) is used as raw material, and a biomimetic mineralization method and a critical point drying method are comprehensively utilized to prepare ready-to-use dry mesoporous mineralized silk fibroin microspheres (mSilMA for short). Silk fibroin is a regularly oriented fiber structure formed by hierarchical assembly of nanofibrils, and contains a large number of polar amino acids. These hydrophilic and polar groups can be tightly combined with positive and negative ions, and can induce inorganic substances to nucleate and grow on the silk fibroin template. The effective loading rate of BMP-2 (500ng) per milligram of mSilMA prepared by the present invention reaches more than 85%. In vitro sustained release detection found that mSilMA microspheres can continuously release BMP-2 in low amounts, and the cumulative release of BMP-2 in vitro for 4 weeks is about 2%, which can achieve long-term low-amount sustained release of BMP-2.

[0088] 2. Preparation method of ready-to-use mesoporous mineralized silk fibroin microspheres

[0089] The present invention provides an optimal preparation method for ready-to-use mesoporous mineralized silk fibroin microspheres capable of long-term, low-volume sustained release of BMP-2, which specifically comprises the following steps:

[0090] 1. Preparation of SilMA hydrogel microspheres by photocrosslinking oil / water emulsification method

[0091] SilMA was dissolved in double distilled water at room temperature to obtain a 20% (W / V) SilMA solution, and a certain volume of LAP solution (ultraviolet light initiator: phenyl (2,4,6-trimethylbenzoyl) lithium phosphate) was added as the aqueous phase, with a final concentration of 0.25% (W / V). The composition of the oil phase was liquid paraffin and Span 80, with a mixing ratio of 1:20; the aqueous phase was added dropwise to the oil phase, with an oil-water ratio of 5:1, and stirred at 400rpm at room temperature, and ultraviolet irradiation was performed during the stirring process. After 10 minutes, stirring and irradiation were stopped, and the microspheres were allowed to stand, and the microspheres were precipitated at the bottom of the beaker. The supernatant (oil phase) was discarded, and the microspheres were washed with 50% isopropanol aqueous solution 3 times, 75% isopropanol aqueous solution 2 times, and 80% isopropanol aqueous solution 1 time; washed with a large amount of water 3 times, and allowed to stand, and the microspheres were precipitated at the bottom of the beaker. The supernatant (water) was discarded and the microspheres were harvested by filtration.

[0092] Among them, the concentration of the SilMA solution is 10%-30%; the dissolution temperature of the SilMA is 25°C-45°C, and in this embodiment, it is preferably 25°C-30°C; the final concentration of the LAP aqueous solution is: 0.1%-0.5% (W / V%); in the oil phase, the mass ratio of Siban 80 to liquid paraffin is 1:10-1:30; the volume ratio of the oil phase to the water phase is 1:1-10:1; the stirring temperature is 25°C-45°C, and in this embodiment, it is preferably 25°C-30°C; the stirring speed is 100rpm-500rpm, and in this embodiment, it is preferably 400rpm-450rpm; the stirring time and ultraviolet irradiation time are 5-15min; the mixing emulsification device of the oil phase and the water phase can adopt a mechanical stirring, a magnetic stirring or a homogenizing stirring device, and in this embodiment, a homogenizing stirring device is preferred.

[0093] 2. Mineralization of SilMA hydrogel microspheres

[0094] The harvested SilMA hydrogel microspheres were immersed in a calcium chloride / phosphoric acid mixed solution with a calcium chloride / phosphoric acid molar ratio of 1.67. After immersion for 24 hours, the solution was filtered and the upper mineralized liquid was discarded. Subsequently, a 15% (W / V) ammonia solution was added, and after reaction for 3 hours, the supernatant solution was filtered and discarded. The prepared mineralized SilMA hydrogel microspheres were then washed with water multiple times.

[0095] The molar ratio of the calcium chloride / phosphoric acid mixed solution is 1.5-2.0, and in this embodiment, it is preferably 1.5-1.7; the immersion time of the mineralizing solution is 12 hours to 48 hours, and in this embodiment, it is preferably 24 hours; the volume fraction of the ammonia solution is 10% to 20%, and in this embodiment, it is preferably 15%; the ammonia action time is 30 minutes to 2 hours.

[0096] 3. Critical point drying of mineralized SilMA hydrogel microspheres

[0097] The mineralized SilMA hydrogel microspheres were dehydrated using a gradient ethanol aqueous solution, the concentration of the ethanol aqueous solution was 30%-50%-70%-90%-100%; the immersion time at each ethanol concentration was 15 minutes; then critical point drying was performed in a critical point dryer for 3 hours, and dry mesoporous mineralized silk fibroin methacrylamide microspheres (abbreviated as mSilMA) were harvested.

[0098] The microspheres are immersed in the ethanol aqueous solution for 15-30 minutes; the critical point drying time is 1-5 hours, and in this embodiment, preferably 3-5 hours.

[0099] 4. Calculation of BMP-2 content bound by mSilMA microspheres

[0100] Weigh 10 mg of mSilMA prepared in step 3, add 500 ng of bone morphogenetic protein (BMP-2) solution, incubate at 4°C for 24 hours, add 5 mL of saline (containing 0.1% bovine serum albumin solution) to wash three times, remove the BMP-2 that failed to bind to the microspheres, collect the washing solution three times, and use enzyme-linked immunosorbent assay to detect the content of BMP-2 in the washing solution. The content of BMP-2 bound to each milligram of microspheres is calculated as follows: (the original amount of BMP-2 added minus the BMP-2 content obtained in the washing solution) / total mass of the microspheres.

[0101] 5. In vitro sustained release detection of BMP-2

[0102] Weigh 10 mg of 20% mSilMA microspheres and 20% SilMA microspheres, add 500 μl of 500 ng BMP-2 solution (solvent is saline containing 0.1% bovine serum albumin), incubate at 4°C for 24 hours, then add 5 mL of saline containing 0.1% bovine serum albumin, wash 3 times at room temperature, and collect 15 mL of washing liquid for 20% mSilMA microspheres and 20% SilMA microspheres. Use BMP-2 enzyme-linked immunosorbent assay kit to detect BMP-2 in the washing liquid that is not bound by the microspheres; it can be seen that the bound BMP-2 is equal to the original amount added (500 ng) minus the content of BMP-2 in the washing liquid.

[0103] 20% mSilMA microspheres and 20% SilMA microspheres combined with BMP-2 were immersed in 5 mL of physiological saline containing 0.1% bovine serum albumin, incubated at 37°C, and the supernatants were collected on days 1, 4, 7, 124, 21, 28, and 35, and the BMP-2 enzyme-linked immunosorbent assay kit was used to detect the content of BMP-2 in the supernatant. The release percentage of BMP-2 at a specific time is: the cumulative release amount of BMP-2 in the supernatant during the time period / the total amount of BMP-2 combined with the microspheres; the cumulative release percentage of BMP-2 is: the sum of all release percentages of BMP-2 during the time period.

[0104] In summary, the preparation process of the dry mesoporous mineralized silk fibroin methacrylamide microspheres (mSilMA) is as follows: Figure 1 The prepared mSilMA has a particle size of 100-500 μm, preferably 250-350 μm in this embodiment; the surface of the mSilMA has interconnected fiber network structures and needle-shaped calcium phosphate materials, and the pore size of the fiber network is 5-100 nm, preferably 10-15 nm in this embodiment.

[0105] Therefore, by adopting the optimal preparation method of the present invention, based on the silk fibroin material with good biocompatibility, coupling the biomimetic mineralization method and the critical point drying method, the long-term low-amount release of BMP-2 in vitro was achieved without the occurrence of early burst release.

[0106] Example 2 Screening of the main components of microspheres and the necessity of the "mesopore channel" structure in microspheres

[0107] In order to obtain the microspheres with the best performance in Example 1 that can release bone morphogenetic protein in a long-term and low amount, the main components of the microspheres were first screened in this example. The specific screening process is as follows (the other operating processes and experimental conditions not mentioned are the best conditions in Example 1):

[0108] 1. Comparison of results under scanning electron microscope

[0109] The main components of the microspheres are silk methacrylamide and gelatin methacrylamide, respectively, to prepare gelatin methacrylamide hydrogel microspheres (GelMA for short) and silk fibroin methacrylamide microspheres (SilMA), and the specific preparation process is as follows:

[0110] The gelatin methacrylamide hydrogel microspheres (GelMA) and silk fibroin methacrylamide microspheres (SilMA) of the same concentration were prepared by UV cross-linking oil / water emulsification method; at the same time, the two hydrogel microspheres were immersed in 30%-50%-70%-90%-100% ethanol aqueous solution for gradient dehydration, and the immersion time for each ethanol concentration was 15 minutes. Subsequently, critical point drying was performed using a critical point dryer for 3 hours, and the dry GelMA and SilMA microspheres were harvested.

[0111] Specific results such as Figure 2 As shown, Figure 2 The surface morphology of GelMA microspheres and SilMA microspheres after critical point drying under a scanning electron microscope. Scanning electron microscope observations show that after the same ethanol gradient dehydration and critical point drying, GelMA hydrogel microspheres do not form a surface-penetrating mesoporous structure, but present a non-porous structure; while the surface of SilMA microspheres forms an interconnected pore structure. Therefore, it can be preliminarily determined that not all materials can form pores through critical point drying.

[0112] In the critical point drying method, the medium uses a phase change method of liquid carbon dioxide-supercritical carbon dioxide-gas carbon dioxide to reduce the surface stress of the interface to zero, which can preserve the fine structure of the sample. Silk fibroin is a natural high-molecular fiber protein extracted from silk and has a fiber structure. Gelatin is a type of protein obtained by partial hydrolysis of collagen fibers. Collagen has a rod-shaped triple helix structure. When it is partially hydrolyzed to prepare gelatin, this triple helix structure of collagen separates and breaks, causing gelatin to lose its fiber structure. It is speculated that because silk fibroin has an original fiber structure, its own fiber network can be reproduced through critical point drying; gelatin itself does not have a relatively complete fiber structure. At the same time, in the process of ethanol gradient dehydration, as water is lost, the network structure of the hydrogel itself gradually becomes dense, and then through critical point drying, the fiber network structure can no longer appear, so the surface is dense and non-porous. Therefore, it is speculated that if the material itself has a fiber structure, a porous structure can be produced through critical point drying; if the material itself does not have a fiber structure, a porous structure cannot be produced through critical point drying.

[0113] In the present invention, the mesoporous channel structure is crucial to prepare hydrogel microspheres that can release BMP-2 in a long-term and low amount. First, the presence of mesopores can greatly increase the loading amount of drugs; second, the interconnected mesoporous channels have extremely high superiority, and the structure is conducive to the diffusion and release of cell active factors inside the microspheres, which can achieve the slow and continuous release of cell active factors and avoid the sudden release of cell active factors, thereby prolonging the action time of cell active factors in the body, improving the utilization efficiency and therapeutic effect of cell active factors, and providing lasting and stable support for processes such as bone repair; on the other hand, the mesoporous structure plays a key role in the material exchange and information transmission between the microspheres and the surrounding environment, enhancing the interaction between the microspheres and the body, and improving the adaptability and biocompatibility of the microspheres in the body.

[0114] Therefore, in this embodiment, silk fibroin methacrylamide that can form a mesoporous structure is preferably used as the main component of the microspheres to achieve a more ideal drug controlled release effect and biological application performance, providing strong technical support and innovative ideas for the development of fields such as bone tissue engineering.

[0115] 2. Comparison of BMP-2 protein loading rate and long-term low-volume sustained release capacity

[0116] 1. Comparison of BMP-2 protein loading rate

[0117] At the same time, in order to further verify the importance of using silk protein materials in the successful preparation of mSilMA with high protein loading rate and long-term low-volume sustained release of bone morphogenetic protein, the gelatin methacrylamide hydrogel microspheres (GelMA for short) and silk protein methacrylamide microspheres (SilMA) in step 1 were used in this embodiment, and GelMA microspheres and mSilMA microspheres were prepared according to the best preparation method in Example 1. After weighing 10 mg of each, 500 μl of 500 ng BMP-2 solution (solvent is saline containing 0.1% bovine serum albumin) was added respectively, incubated at 4°C for 24 hours, and then 5 mL of saline containing 0.1% bovine serum albumin was added respectively, and washed at room temperature for 3 times, then 15 mL of washing liquid can be collected for GelMA microspheres and mSilMA microspheres respectively. BMP-2 enzyme-linked immunosorbent assay kit (purchased from Shenzhen Xinbosheng Biotechnology Co., Ltd., model: EHC172.96) was used to detect BMP-2 not bound by microspheres in the washing liquid. The amount of BMP-2 bound per milligram of microspheres is calculated as (the original amount added (500 ng) minus the amount of BMP-2 in the cleaning solution) / total mass of microspheres. The specific amounts of BMP-2 bound to different microspheres are shown in Table 1.

[0118] 2. Comparison of the long-term, low-volume sustained-release capacity of BMP-2

[0119] As above, the GelMA microspheres and mSilMA microspheres respectively combined with BMP-2 were immersed in 5 mL of physiological saline containing 0.1% bovine serum albumin, incubated at 37°C, and the supernatants were collected at 1, 4, 7, 14, 21, 28, and 35 days, and the BMP-2 enzyme-linked immunosorbent assay kit was used to detect the content of BMP-2 in the supernatant. The release percentage of BMP-2 at a specific time is: the cumulative release amount of BMP-2 in the supernatant / the total amount of BMP-2 combined with the microspheres during the time. The in vitro release capacity of BMP-2 of different microspheres within a certain period of time is specifically shown in Table 2.

[0120] 3. Experimental results

[0121] The results of the above different experiments are shown in Table 1 and Table 2:

[0122] Table 1. Content of BMP-2 bound to different microspheres

[0123] name Bound BMP-2 content BMP-2 protein loading rate mSilMA Microspheres 44.34ng / mg 88.68% GelMA Microspheres 20.85ng / mg 41.70%

[0124] Table 2. In vitro release capacity of BMP-2 of different microspheres within a certain period of time

[0125]

[0126] As can be seen from Tables 1 and 2, only when silk methacrylamide is used as the main component and SilMA microspheres with a surface-penetrating mesoporous structure are successfully prepared, the BMP-2 protein loading rate can reach 88.68%, and BMP-2 can be continuously released in low amounts, with a cumulative release of about 2.5% of BMP-2 in vitro for 4 weeks; when other components are used, the effect of the present invention cannot be achieved. Therefore, in this embodiment, silk methacrylamide that can form mesopores is preferably used as the main component of the microspheres.

[0127] Example 3 Screening of different drying methods when preparing dry SilMA

[0128] In order to obtain the mSilMA with the best performance in Example 1, the drying method of the mineralized SilMA hydrogel microspheres in the preparation process of mSilMA was screened in this example. The specific screening process is as follows (the other operating processes and experimental conditions not mentioned are the best conditions in Example 1):

[0129] 1. Comparison of results under scanning electron microscope

[0130] The prepared mineralized SilMA hydrogel microspheres were dehydrated by freeze drying and critical point drying, respectively, and the obtained dry SilMA microspheres were observed by scanning electron microscopy.

[0131] 1. Freeze drying: The prepared mineralized SilMA hydrogel microspheres were directly pre-frozen in a -80°C refrigerator for 24 h, and then dried using a freeze dryer. Dry non-porous SilMA microspheres were harvested after 48 h.

[0132] 2. Critical point drying: The prepared mineralized SilMA hydrogel microspheres were immersed in 30%-50%-70%-90%-100% ethanol aqueous solution for gradient dehydration, and the immersion time at each ethanol concentration was 15 min; then critical point drying was performed using a critical point dryer for 3 hours to harvest dry mesoporous mineralized silk fibroin methacrylamide microspheres (mSilMA).

[0133] Specific results such as Figure 3 As shown, Figure 3 The surface morphology of dry SilMA microspheres prepared by freeze drying and critical point drying methods is shown. Figure 3 It can be seen that the mSilMA microspheres prepared by the critical point drying method have a smooth and uniform surface, no adhesion phenomenon, and the surface of the microspheres has uniformly distributed mesopores; the uniform mesoporous structure is conducive to the loading and sustained release of drugs, and can provide a more stable and controllable release environment for drugs such as BMP-2, thereby better exerting the role of drugs and improving the therapeutic effect.

[0134] However, the dry SilMA microspheres prepared by freeze-drying method not only fail to form mesopores on the surface of the microspheres, resulting in limited drug loading and sustained release performance, but also adhesion between the microspheres, resulting in a rough surface; this rough surface and adhesion phenomenon may affect the dispersibility and stability of the microspheres, and thus affect their effectiveness in practical applications.

[0135] 2. Comparison of BMP-2 protein loading rate and long-term low-volume sustained release capacity

[0136] 1. Comparison of BMP-2 protein loading rate

[0137] At the same time, in order to further verify the importance of using a drying method (critical drying method) in the successful preparation of mSilMA with high protein loading rate and long-term low-volume sustained release of bone morphogenetic protein, 10 mg of the following microspheres were weighed in this example:

[0138] 1. Dry non-porous mineralized SilMA microspheres prepared by freeze drying in step 1;

[0139] 2. Dry mesoporous mineralized SilMA microspheres prepared by critical point drying (mSilMA microspheres prepared by the best preparation method in Example 1);

[0140] 3. and undried mineralized SilMA hydrogel microspheres (the preparation method of the microspheres is specifically the best preparation method in Example 1, except that the drying step is omitted);

[0141] And add 500μl 500ng BMP-2 solution (the solvent is saline containing 0.1% bovine serum albumin), incubate at 4℃ for 24h, then add 5mL of saline containing 0.1% bovine serum albumin, wash 3 times at room temperature, then 15mL of cleaning solution for dry non-porous mineralized SilMA microspheres, dry mesoporous mineralized SilMA microspheres, and mineralized SilMA hydrogel microspheres. Use BMP-2 enzyme-linked immunosorbent assay kit to detect BMP-2 not bound by microspheres in the cleaning solution. The bound BMP-2 per milligram of microspheres is calculated as: (the original amount added (500ng) minus the content of BMP-2 in the cleaning solution) / total mass of microspheres. The content of BMP-2 bound to different microspheres is shown in Table 3.

[0142] 2. Comparison of the long-term, low-volume sustained-release capacity of BMP-2

[0143] As above, the dry non-porous SilMA microspheres and mSilMA microspheres respectively combined with BMP-2 were immersed in 5 mL of physiological saline containing 0.1% bovine serum albumin, incubated at 37°C, and the supernatants were collected at 1, 4, 7, 14, 21, 28, and 35 days, and the BMP-2 enzyme-linked immunosorbent assay kit was used to detect the content of BMP-2 in the supernatant. The release percentage of BMP-2 at a specific time is: the cumulative release amount of BMP-2 in the supernatant / the total amount of BMP-2 combined with the microspheres during the time. The in vitro release capacity of BMP-2 of different microspheres within a certain period of time is specifically shown in Table 4.

[0144] 3. Experimental results

[0145] The results of the above different experiments are shown in Table 3 and Table 4:

[0146] Table 3. Content of BMP-2 bound to different microspheres

[0147] Different drying methods Bound BMP-2 content BMP-2 protein loading rate Dry non-porous mineralized SilMA microspheres (freeze-dried) 36.22ng / mg 72.44% Dry mesoporous mineralized SilMA microspheres (critical drying) 44.34ng / mg 88.68% Mineralized SilMA hydrogel microspheres (undried) 32.89ng / mg 65.78%

[0148] Table 4. In vitro release capacity of BMP-2 of different microspheres within a certain period of time

[0149]

[0150] As can be seen from Tables 3 and 4, only when the critical drying method is used can the SilMA microspheres with a surface-penetrating mesoporous structure be successfully prepared, and the BMP-2 protein loading rate can reach 88.68%. At the same time, BMP-2 is continuously released in low amounts, and about 2.51% of BMP-2 is cumulatively released in vitro for 4 weeks; when other drying methods are used or no drying is performed, the effect of the present invention cannot be achieved, the BMP-2 protein loading rate is significantly reduced, and the in vitro controlled release ability of BMP-2 is also significantly reduced. Therefore, in this embodiment, the critical point drying method is preferably used to prepare mSilMA.

[0151] Example 4 Screening of different mineralization methods in the preparation of mineralized SilMA hydrogel microspheres

[0152] In order to obtain the mSilMA with the best performance in Example 1, different mineralization methods were screened during the preparation of mineralized SilMA hydrogel microspheres in this example. The specific screening process is as follows (the other operating processes and experimental conditions not mentioned are the best conditions in Example 1):

[0153] 1. 10x simulated body fluid method (abbreviated as 10×SBF method): Simulated body fluid (SBF) is the most commonly used solution for in vitro simulation and the basis for in vitro simulation experiments. It is designed based on the ion concentration of human plasma for the purpose of testing the biological activity of materials. The principle of SBF is that after being implanted into the human body, artificially synthesized materials can connect with bones by forming a bone-like apatite layer on the surface; similarly, artificial materials can also form hydroxyapatite in SBF with a similar ion concentration to human plasma, which means that the material has biological activity.

[0154] Prepare 500 mL of 10-fold simulated body fluid: sodium chloride 1000 mmol / L, potassium chloride 5 mmol / L, calcium chloride dihydrate 25 mmol / L, magnesium chloride hexahydrate 5 mmol / L, sodium dihydrogen phosphate 10 mmol / L, pH = 7.2-7.4.

[0155] 2. Nanocluster method (PILP method): Weigh 2.15 g of polyacrylic acid (PAA), 1.08 g of polyaspartic acid (PASP) and 0.362 g of disodium hydrogen phosphate in a 100 mL beaker, add 25 mL of ultrapure water, put in a rotor, seal with tin foil, and stir at room temperature overnight. A dark yellow viscous solution A is obtained.

[0156] Weigh 3 g of PASP, add 10 mL of double distilled water, and fully dissolve and mix.

[0157] Under magnetic stirring, add 0.1 mL of PASP solution to the beaker, slowly drop 2 mL of 0.1 mol / L CaCl2 solution, and slowly drop 2 mL of solution A with a syringe until fully stirred. Slowly drop 0.4 mL of 3 mol / L NaOH solution, and stir thoroughly to mix. The prepared nanoclusters can be stored at 4°C for 2 weeks.

[0158] 3. Calcium chloride / phosphoric acid-ammonia water reaction method (Ca / P method for short): prepare 500 mL of 1x calcium chloride / phosphoric acid solution, with a calcium chloride / phosphoric acid molar ratio of 1.67, a calcium chloride concentration of 0.167 mol / L, a phosphoric acid concentration of 0.1 mom / L, and an ammonia water volume fraction of 15% (V / V).

[0159] An equal amount of SilMA microspheres were immersed in the above three mineralization solutions for 24 hours. For the 10×SBF method and the PILP method, after immersion for 24 hours, the microspheres were washed with water three times, and the microspheres were directly collected, dehydrated with ethanol gradient, and then critically dried. For the Ca / P method, the microspheres were filtered after immersion for 24 hours, and the upper mineralization solution was discarded. Subsequently, a 15% (W / V) ammonia solution was added, and after reaction for 3 hours, the supernatant was filtered and discarded. The prepared mineralized microspheres were then washed with water three times, dehydrated with ethanol gradient, and then critically dried.

[0160] Specific results such as Figure 4 As shown, Figure 4 The structure and content of calcium phosphate formed on the surface of SilMA microspheres by different mineralization methods are shown. Figure 4 It can be seen that the Ca / P method can form a more uniform and denser calcium phosphate mineralization coating on the surface of SilMA microspheres, and a more uniform and denser calcium phosphate mineralization coating can enhance the stability and mechanical strength of the microspheres, improve the compatibility and binding ability of the microspheres with bone tissue, and help to better promote bone regeneration and repair processes; in addition, the uniform and high-density coating can more effectively control the release rate of the drug, provide a more stable loading environment for the drug, thereby improving the therapeutic effect of the drug. Therefore, in this embodiment, the Ca / P method is preferably used as the mineralization method of SilMA microspheres.

[0161] Example 5 Screening of different mineralization concentrations in the preparation of mineralized SilMA hydrogel microspheres

[0162] In order to obtain the mSilMA with the best performance in Example 1, different mineralization concentrations in the Ca / P method were screened during the preparation of mineralized SilMA hydrogel microspheres in this example, and the effects of different mineralization concentrations on the SilMA microspheres and the surface calcium phosphate mineralization layer were studied. The specific screening process is as follows (the other operating processes and experimental conditions not mentioned are the optimal conditions in Example 1):

[0163] First, the different mineralization concentrations in the Ca / P method are defined as follows:

[0164] 1x Ca / P mineralization solution: calcium chloride / phosphoric acid molar ratio is 1.67, calcium chloride concentration is 0.167 mol / L, phosphoric acid concentration is 0.1mom / L;

[0165] 5 times Ca / P mineralization solution means that the concentration of calcium chloride and phosphoric acid increases 5 times at the same time: the concentration of calcium chloride is 0.835 mol / L, and the concentration of phosphoric acid is 0.5 mom / L;

[0166] 10 times Ca / P mineralization solution means that the concentrations of calcium chloride and phosphoric acid are increased by 10 times at the same time: the concentration of calcium chloride is 1.67 mol / L, and the concentration of phosphoric acid is 1.0 mom / L;

[0167] The same mineralization steps were used for mineralization and subsequent critical point drying: 20% SilMA microspheres were immersed in the above three mineralization solutions for 24 hours and then filtered to discard the upper mineralization solution; then 15% (W / V) ammonia solution was added, reacted for 3 hours, the supernatant was filtered and discarded, and then the prepared mineralized microspheres were washed with water 3 times, dehydrated with ethanol gradient, and then critically dried.

[0168] Specific results such as Figure 5 As shown, Figure 5 The effects of three concentrations of Ca / P mineralization solution on the structure and surface mineralization coating of 20% SilMA microspheres are shown. It can be seen that when other conditions remain unchanged, increasing the concentration of Ca / P mineralization solution will lead to the destruction of the microsphere structure, and the calcium-phosphorus coating still maintains a needle-like structure. As the concentration of Ca / P mineralization solution increases, the coating density increases. Since 5 times and 10 times of Ca / P mineralization solution have obvious damage to the microsphere structure, 1 times of calcium-phosphorus mineralization solution is preferred in this embodiment. At this concentration, the complete structure of the microsphere is retained, and a relatively evenly distributed needle-like calcium-phosphorus coating can be present on the surface of the 20% SilMA microsphere, and the mesoporous channels of the microsphere itself are not completely blocked by the needle-like calcium-phosphorus coating.

[0169] At the same time, based on the 1x Ca / P mineralization method, this example also conducted a nitrogen physical adsorption test on the prepared dry mesoporous 20% SilMA microspheres (referred to as 20% SilMA) and dry mesoporous mineralized 20% SilMA microspheres (referred to as 20% mSilMA) to compare the pore size distribution of the two, so as to further understand the effect of mineralization treatment on the pore size of the microspheres and evaluate the changes in the physical properties of the microspheres during the mineralization process. The specific results are as follows: Figure 6 A in Figure 6 B and Figure 6 As shown in C, from Figure 6 B and Figure 6In C, it can be seen that the average pore size of the surface of 20% mSilMA microspheres is about 10nm, while the average pore size of 20% SilMA is about 19nm (as shown in Figure 6 A and Figure 6 As shown in C in the figure). Therefore, it can be seen that the concentration of 1 times Ca / P mineralization solution is more appropriate, and mineralization treatment will reduce the pore size of the microspheres. Within the appropriate range, the pore size of the microsphere surface is smaller, which has the following advantages: (1) It can have better controlled release performance: smaller pore size can more effectively control the release rate and amount of drugs or bioactive molecules, so that they can be released continuously and stably for a longer time, improving the therapeutic effect; (2) Enhanced stability: smaller pore size may make the microsphere structure more stable, reduce the impact of the external environment on the internal load material, and improve the stability of the microspheres during storage and use; (3) Improved selectivity: It can more selectively allow molecules of a specific size to pass or be adsorbed, thereby achieving more accurate delivery of drugs or bioactive molecules; (4) Reduced burst release: Reduced the sudden and large-scale release of drugs or bioactive molecules in the initial stage, making the release of drugs or bioactive molecules more uniform and controllable.

[0170] Therefore, it can be seen that in the present invention, mineralization treatment is an indispensable step. Only by mineralizing the dry mesoporous SilMA microspheres and adopting the mineralization method and the 1-fold Ca / P mineralization method, can mSilMA with a complete structure and a uniform mineralized coating be prepared, so as to achieve the best effect of optimizing the physical properties of the microspheres and the controlled release performance of BMP-2, and provide a more ideal material choice for applications in related fields such as bone repair.

[0171] Example 6 Necessity of the mineralization step for the in vitro controlled release of BMP-2 by mSilMA of the present invention

[0172] In this example, the surface morphologies of 20% mSilMA microspheres (dry mesoporous mineralized microspheres) and 20% SilMA microspheres (dry mesoporous microspheres) prepared by the 1x Ca / P mineralization method were further compared, and the characteristic elements of the mineralized coating on the surface of 20% mSilMA microspheres were detected and verified. Figure 7 As shown in A.

[0173] At the same time, in order to verify the necessity of mineralization for the preparation of mSilMA in the present invention, the following microspheres were also taken in this example:

[0174] 1. 20% mSilMA microspheres (microspheres prepared by the best preparation method in Example 1);

[0175] 2. 20% SilMA microspheres (the dry mesopores are not mineralized, and the remaining steps are the same as the best preparation method in Example 1);

[0176] 3. Using other mineralization methods: microspheres prepared by the 10-fold simulated body fluid method in Example 4;

[0177] 4. Using other mineralization methods: microspheres prepared by the nanocluster method in Example 4;

[0178] 5. Microspheres prepared by using other mineralization concentrations: 5 times the Ca / P mineralization solution in Example 5;

[0179] 6. Microspheres prepared using other mineralization concentrations: 10 times the Ca / P mineralization solution in Example 5;

[0180] The differences in the in vitro controlled release ability of BMP-2 of the microspheres prepared by the above-mentioned different methods were compared and tested. The steps of BMP-2 in vitro release detection are as follows:

[0181] (1) Comparison of BMP-2 protein loading rate: Weigh the above different microspheres respectively, add 500μl 500ng BMP-2 solution (solvent is saline containing 0.1% bovine serum albumin), incubate at 4℃ for 24h, then add 5mL saline containing 0.1% bovine serum albumin, wash 3 times at room temperature, and collect 15mL washing liquid for the above 6 different microspheres. Use BMP-2 enzyme-linked immunosorbent assay kit to detect BMP-2 in the washing liquid that is not bound by the microspheres. The bound BMP-2 is equal to the original added amount (500ng) minus the content of BMP-2 in the washing liquid.

[0182] (2) Comparison of the long-term, low-volume sustained-release ability of BMP-2: The above microspheres respectively combined with BMP-2 were immersed in 5 mL of physiological saline containing 0.1% bovine serum albumin, incubated at 37°C, and the supernatant was collected at 1, 4, 7, 14, 21, 28, and 35 days, and the BMP-2 enzyme-linked immunosorbent assay kit was used to detect the content of BMP-2 in the supernatant. The release percentage of BMP-2 at a specific time is: the cumulative release amount of BMP-2 in the supernatant during the time period / the total amount of BMP-2 combined with the microspheres%.

[0183] The results of the above different experiments are shown in Tables 5, 6 and Figure 7 As shown in B:

[0184] Table 5. Content of BMP-2 bound to different microspheres

[0185] Different mineralization methods / conditions Bound BMP-2 content BMP-2 protein loading rate 20% mSilMA microspheres 44.34ng / mg 88.68% 20% SilMA microspheres (dry mesoporous and unmineralized) 30.67ng / mg 61.74% SilMA-1 microspheres (10 times simulated body fluid method) 32.17ng / mg 64.34% SilMA-2 microspheres (nanocluster method) 31.29ng / mg 61.29% SilMA-3 microspheres (5 times Ca / P mineralization solution) 40.74ng / mg 81.47% SilMA-4 microspheres (10 times Ca / P mineralization solution) 42.19ng / mg 84.38%

[0186] Table 6. In vitro release capacity of BMP-2 of different microspheres within a certain period of time

[0187]

[0188] It can be seen from Tables 5 and 6 that only when the Ca / P method is used as the mineralization method and the mineralization concentration is 1 times the Ca / P mineralization solution, can complete mSilMA microspheres with a surface-penetrating mesoporous channel structure be successfully prepared, and the BMP-2 protein loading rate can reach 88.68%, while BMP-2 can be continuously released in low amounts, with a cumulative release of about 2.5% of BMP-2 in vitro for 4 weeks; when other mineralization methods, mineralization concentrations or no mineralization treatment are used, the effects of the present invention cannot be achieved, the BMP-2 protein loading rate is significantly reduced, and the in vitro controlled release ability of BMP-2 is also significantly reduced.

[0189] At the same time, from Figure 7 It can also be seen from Figure B that the in vitro BMP-2 sustained-release test found that 20% mSilMA microspheres could sustain low-amount sustained-release of BMP-2, with a cumulative release of about 2% BMP-2 in vitro for 4 weeks, while 20% SilMA microspheres failed to sustain long-term release of BMP-2, but reached a plateau in about 3 weeks. This may be because the adsorption / dissolution of the drug by the mesopores reached a certain equilibrium, resulting in incomplete release.

[0190] Therefore, in this embodiment, the critical point drying method is preferably used to prepare mSilMA.

[0191] Example 6 Screening of different SilMA solution concentrations during the preparation of SilMA

[0192] In order to obtain the mSilMA with the best performance in Example 1, the concentration of the SilMA solution was screened during the preparation of SilMA in this example. The specific screening process is as follows (the other operating processes and experimental conditions not mentioned are the best conditions in Example 1):

[0193] 1. Preparation of microspheres with different concentrations

[0194] 1. The concentration of SilMA solution is 10% (W / V%)

[0195] Dissolve SilMA in double distilled water at 25°C to obtain a 10% (W / V%) SilMA solution, add a certain volume of LAP solution as the aqueous phase, and the final concentration is 0.25% (W / V%). The composition of the oil phase is liquid paraffin and Span 80, with a mixing ratio of 1:20; add the aqueous phase dropwise to the oil phase, with an oil-water ratio of 5:1, stir at 400rpm at 25°C, and irradiate with ultraviolet light during stirring. Stop stirring and irradiation after 10 minutes, let it stand, and the microspheres will settle at the bottom of the beaker. Discard the supernatant (oil phase), wash 3 times with 50% isopropanol aqueous solution, wash 2 times with 75% isopropanol aqueous solution, and wash once with 80% isopropanol aqueous solution; wash 3 times with a large amount of water, let it stand, and the microspheres will settle at the bottom of the beaker. Discard the supernatant (water) and filter to harvest the microspheres. The 10% SilMA hydrogel microspheres were immersed in 30%-50%-70%-90%-100% ethanol aqueous solution for gradient dehydration, and the immersion time at each ethanol concentration was 15 minutes; then critical point drying was performed in a critical point dryer for 3 hours to harvest 10% dry mesoporous silk fibroin methacrylamide microspheres (abbreviated as 10% SilMA).

[0196] 2. The concentration of SilMA solution is 20% (W / V%)

[0197] Dissolve SilMA in double distilled water at 25°C to obtain a 20% (W / V%) SilMA solution, add a certain volume of LAP solution as the aqueous phase, and the final concentration is 0.25% (W / V%). The composition of the oil phase is liquid paraffin and Span 80, with a mixing ratio of 1:20; add the aqueous phase dropwise to the oil phase, with an oil-water ratio of 5:1, stir at 400rpm at 25°C, and irradiate with ultraviolet light during stirring. Stop stirring and irradiation after 10 minutes, let it stand, and the microspheres will settle at the bottom of the beaker. Discard the supernatant (oil phase), wash with 50% isopropanol aqueous solution 3 times, 75% isopropanol aqueous solution 2 times, and 80% isopropanol aqueous solution 1 time; wash with a large amount of water 3 times, let it stand, and the microspheres will settle at the bottom of the beaker. Discard the supernatant (water) and filter to harvest the microspheres. The 20% SilMA hydrogel microspheres were immersed in 30%-50%-70%-90%-100% ethanol aqueous solution for gradient dehydration, and the immersion time at each ethanol concentration was 15 minutes; then critical point drying was performed in a critical point dryer for 3 hours to harvest 20% dry mesoporous silk fibroin methacrylamide microspheres (referred to as 20% SilMA).

[0198] 3. The concentration of SilMA solution is 30% (W / V%)

[0199] Dissolve SilMA in double distilled water at 25°C to obtain a 30% (W / V%) SilMA solution, add a certain volume of LAP solution as the aqueous phase, and the final concentration is 0.25% (W / V%). The composition of the oil phase is liquid paraffin and Span 80, with a mixing ratio of 1:20; add the aqueous phase dropwise to the oil phase, with an oil-water ratio of 5:1, stir at 400rpm at 25°C, and irradiate with ultraviolet light during stirring. Stop stirring and irradiation after 10 minutes, let it stand, and the microspheres will settle at the bottom of the beaker. Discard the supernatant (oil phase), wash with 50% isopropanol aqueous solution 3 times, 75% isopropanol aqueous solution 2 times, and 80% isopropanol aqueous solution 1 time; wash with a large amount of water 3 times, let it stand, and the microspheres will settle at the bottom of the beaker. Discard the supernatant (water) and filter to harvest the microspheres. The 30% SilMA hydrogel microspheres were immersed in 30%-50%-70%-90%-100% ethanol aqueous solution for gradient dehydration, and the immersion time at each ethanol concentration was 15 minutes; then critical point drying was performed in a critical point dryer for 3 hours to harvest 30% dry mesoporous silk fibroin methacrylamide microspheres (referred to as 30% SilMA).

[0200] 2. Results Analysis

[0201] The swelling test and surface pore size of the dry mesoporous silk fibroin methacrylamide microspheres prepared by using SilMA solutions of different concentrations were statistically analyzed. The specific results are as follows:

[0202] 1. Swelling performance test

[0203] Weigh the same mass of 10%, 20%, and 30% dry mesoporous SilMA microspheres, soak them in an equal volume of phosphate buffer for 48 hours, filter the supernatant, harvest the microspheres, and weigh them. The swelling properties of mesoporous SilMA microspheres at different concentrations are preliminarily defined by the mass percentage increase of each concentration.

[0204] Figure 8 The swelling performance results of SilMA microspheres with A of 10%, 20%, and 30% are shown in the figure. Figure 8 As shown in Figure A, the 10% SilMA microspheres have the strongest water absorption and swelling ability. They are easily swollen and broken within 1 week of immersion and lose their structural integrity, which indicates that they are not stable enough and are not suitable for subsequent treatment. However, there is no obvious difference in the water absorption and swelling ability of 20% and 30% SilMA microspheres.

[0205] 2. Statistical analysis of surface pore size

[0206] Based on the surface structure scanning electron microscopy images of mesoporous SilMA microspheres with different concentrations, the surface pore diameters of mesoporous SilMA microspheres of each concentration were measured and counted using ImageJ software, and statistically analyzed using GraphPad Prism software.

[0207] Fig. 9 The SEM results of 10%, 20% and 30% mesoporous SilMA microspheres were obtained by statistical analysis of the SEM results. Figure 8 The result shown in B is from Figure 8 As shown in Figure B, the surface pore size of 10% SilMA microspheres is the largest, with an average pore size of about 100nm, the surface pore size of 20% SilMA microspheres is about 20nm, and the surface average pore size of 30% SilMA microspheres is about 5nm. The molecular diameter of bone morphogenetic protein is about 10nm. Only 20% SilMA microspheres with a surface pore size of about 20nm can accommodate the entry of bone morphogenetic protein and limit its excessive release to a certain extent, which helps to achieve a better controlled release effect. The surface average pore size of 30% SilMA microspheres is about 5nm. For bone morphogenetic protein with a molecular diameter of about 10nm, the pore size is too small, which is not conducive to the effective loading and subsequent release of bone morphogenetic protein.

[0208] Therefore, considering the swelling properties and surface pore size distribution of SilMA microspheres with different concentrations, 20% SilMA microspheres performed relatively balanced and ideal in terms of stability, bone morphogenetic protein loading and controlled release. Therefore, 20% SilMA microspheres were preferred for the next step of biomimetic mineralization.

[0209] Example 7 Screening of different preparation methods for preparing SilMA

[0210] In order to obtain the mSilMA with the best performance in Example 1, different preparation methods were screened during the preparation of SilMA in this example. The specific screening process is as follows (the other operating processes and experimental conditions not mentioned are the best conditions in Example 1):

[0211] 1. UV cross-linking oil / water emulsification method (mechanical stirring): the specific preparation steps are as shown in Example 1;

[0212] 2. Photo-cross-linking 3D printing technology: SilMA is prepared using photo-cross-linking 3D printing technology;

[0213] The specific results of SilMA obtained by different preparation methods are as follows Fig.10 A and Fig.10 As shown in B, Fig.10 A in the figure is a light microscopic image of 20% SilMA hydrogel microspheres prepared by the photo-crosslinked oil / water emulsification method (mechanical stirring); Fig.10 B is a light microscopic image of 20% SilMA hydrogel microspheres prepared by photo-crosslinking 3D printing technology. Fig.10It can be seen that the SilMA prepared by the UV-crosslinked oil / water emulsification method (mechanical stirring) of the present invention has significant advantages in terms of yield and sphericity compared with the microspheres prepared by the photo-crosslinked 3D printing technology; the microspheres prepared by the photo-crosslinked 3D printing technology are easy to adhere and have poor sphericity, and are mostly cylindrical.

[0214] In addition, the mechanical stirring method adopted in the present invention can change parameters such as the oil / water ratio and the stirring speed, thereby successfully preparing microspheres with a particle size range of 1μm-1000μm. However, the photo-cross-linking 3D printing technology cannot print and form microspheres below 100μm, and can only print microspheres of specific sizes, such as 200μm, 400μm, etc. In addition, the number of printed microspheres is limited by the volume of the printing ink and the size of the printable stage.

[0215] Therefore, in this embodiment, the UV-crosslinked oil / water emulsification method (mechanical stirring) is preferably used to prepare SilMA, which has the best yield, sphericity, controllability of particle size range and other properties, can better meet the needs of practical applications, and lays a solid foundation for the subsequent preparation of mSilMA with excellent performance.

[0216] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A controlled release carrier, characterized in that: The controlled release carrier is a ready-to-use mesoporous mineralized silk fibroin microsphere. In the ready-to-use mesoporous mineralized silk fibroin microsphere, the main component has a fiber structure, the microsphere has a mesoporous channel structure, and the surface of the microsphere includes a mineralized coating.

2. The controlled release carrier according to claim 1, characterized in that The main component includes silk fibroin; the silk fibroin is silk fibroin methacrylamide.

3. The controlled release carrier according to claim 2, characterized in that The mineralized coating is needle-shaped calcium phosphate; the pore size of the mesoporous channel is 5-50nm.

4. The controlled release carrier according to claim 3, characterized in that The controlled release carrier is loaded with active proteins, which include any one or more of BMP-2, VEGF, FGF, and TGF-β.

5. The controlled release carrier according to claim 1, characterized in that The mineralized coating is prepared by the Ca / P method, the mineralization concentration is 1 times Ca / P mineralizing solution, and in the 1 times Ca / P mineralizing solution, the molar ratio of calcium chloride to phosphoric acid is 1.5-2.

0.

6. The controlled release carrier according to claim 1, characterized in that The controlled release carrier is firstly prepared by ultraviolet light cross-linking oil / water emulsification method and mechanical stirring, and then prepared by mineralization and drying steps, wherein the drying is a critical drying method.

7. The controlled release carrier according to claim 6, characterized in that In the UV-crosslinked oil / water emulsification method, the aqueous phase includes a mixed solution of a SilMA solution and a LAP solution, and the oil phase includes liquid paraffin and Span 80. In the oil phase, the mass ratio of Span 80 to liquid paraffin is 1:10-1:

30.

8. The controlled release carrier according to claim 7, characterized in that The volume ratio of the oil phase to the water phase is 1:1-10:

1.

9. Use of a controlled release carrier for preparing a preparation for improving bone repair ability or promoting bone regeneration, characterized in that: The controlled release carrier according to any one of claims 1 to 8 is used to load active proteins, thereby preparing a preparation for improving bone repair ability or promoting bone regeneration.

10. Use of a controlled release carrier for preparing a preparation for improving the long-acting low-dose sustained release ability of BMP-2 or reducing the burst release ability of BMP-2, characterized in that: The controlled release carrier according to any one of claims 1 to 8 is used to load active proteins, thereby preparing a preparation that improves the long-acting low-dose sustained release ability of BMP-2 or reduces the burst release ability of BMP-2.

Citation Information

Patent Citations

  • Preparation method and use of surface mesoporous silk fibroin microsphere drug slow-release carrier

    CN104825398A

  • Strontium-doped porous silk fibroin microsphere and preparation method thereof

    CN108553690A

  • Preparation method and application of surface composite coating titanium mesh

    CN114699552A

  • Development of silk based bioinks for 3D printing and uses thereof

    IN201831038727A

  • Hyaluronic acid-calcium phosphate composite for growth factor support and method for producing same

    US20150182666A1